FRENCH PROTESTANTISM AND ITS AMBIVALENT ATTITUDE TOWARD CULTURE - Paul Wells (STTRII, 2019)
Protestantism in France has an ambiguous attitude to the surrounding culture, because of its position as a small minority. The other forces present are Roman Catholic authoritarianism and the liberal free-thinking of Enlightenment humanism, represented by the likes of Voltaire and Rousseau. The paradox is that since the Revolution in 1789, which was anti-royal and anti-religious, when Protestantism has sided with the majority Roman Church it has undermined its Reformed identity, and when it has sided with libertarian free-thinking it has undermined its Christian identity. This remains a feature of French Protestantism until the present day. As a result of this tension, the thought of one of France’s greatest thinkers, John Calvin, became virtually unknown, not only in French culture and society as a whole, but also within French Protestantism itself. KEYWORDS: Protestant, Reformed, French, Catholic